Long-Term Social Isolation-Induced Autophagy Inhibition and Cell Senescence Aggravate Cognitive Impairment in D(+)Galactose-Treated Male Mice - Wang, Bin; Ntim, Michael; Xia, Min; Wang, Ying; Lu, Jin-cheng; Yang, Jin-Yi; Li, Shao (Frontiers in Aging Neuroscience, 2022)
Aging is associated with physiological and pathological changes and present health complications such as dementia. Isolation has also been associated with the experience of growing old. Both have been linked individually to the incidence of cognitive decline. In this present study, the effects of these 2 phenomena are looked at in animal models where aging was induced with D(+) galactose in mice undergoing Long-term post-weaned social isolation (L-PWSI). Assessing cognitive function using Y-maze, Morris water maze, and passive avoidance tests confirmed that cognition is impaired in either of the treatment but worsened when the L-PWSI mice were subjected to D(+) galactose treatment. Also, synaptic proteins NR2B and PSD95 were significantly reduced in the L-PWSI and D(+) galactose-treated mice. Our previous study revealed that autophagy deficit is involved in cognitive impairment in the L-PWSI model. Here, we first report the inhibited cell cycle (elevated p16) in L-PWSI, combined with the decreased autophagy (elevated p62), aggravates cognitive impairment in D(+)galactose-treated mice. Beyond these, the autophagy and cell cycle mechanisms linking isolation and aging need further research. The close association between isolation and aging in humans is very real and needs much research attention going forward for possible therapeutic interventions.